Awareness on Social Health Insurance Scheme among Locals in Bhaktapur Municipality - Shrestha, Marina Vaidya; Manandhar, Naresh; Dhimal, Meghnath; Joshi, Sunil Kumar (Journal of Nepal Health Research Council, 2020)
Background: Illnesses impose a huge economic burden on individuals and families. Costly health care also discourages people from using health services thereby generating prolonged or worsened health problems. The recently endorsed National Health Insurance Policy forecasts the integration of all social health protection schemes thereby ultimately achieving universal coverage. The aim of this study was to find out the awareness of health insurance and evaluate source of information about health insurance. Methods: A cross sectional study was conducted on 385 participants from 5 randomly selected wards of Bhaktapur Municipality on July 2019. Households with health insurance were selected. The interview was taken either from the head of the family or the family member who takes financial decisions in the house. Face to face interview was taken in local language (Newari). Good and poor categories on awareness were developed. Descriptive statistics was applied. Results: Good awareness of social health Insurance scheme was found among 335(87.2%) participants. 99% of the participants showed the importance of social health insurance. The main source of information was insurance agents (47.3%) and female community health volunteers (28.6%). Regarding benefits of opting health insurance, 66.5 % of the participants stated that it would reduce out-of-pocket expenditure. 65.5% opined that it would help in case of emergency medical situations. About 91.9% of respondents wanted to renew their health insurance in future also. Conclusions: Awareness regarding health insurance was found good, which shows the positive acceptance of social health Insurance scheme by community. Insurance agent and hemale community health volunteers (FCHV) seemed to have played an important role in dissemination of information. Keywords: Awareness; Bhaktapur municipality; health insurance